NEW POSSIBILITIES IN TRIBAL LITERARY RESEARCH - P, Dr. Palaiah (ShodhKosh: Journal of Visual and Performing Arts, 2024)
There are so many elements that we do not see in the tribal communities that are disappearing in the present day which needs to be recorded. A lot of studies have already been done in universities about tribal communities, socially, economically and traditionally, but there are so many aspects that are hidden in these that we do not see. , about Tribal Nyaya Panchayat, about Tribal Artists, about Tribal Arts, about Tribal Diets, about Tribal Rituals, about Tribal Culture-Laballi Relations. A study of tribal traditional herbal medicine practices, tribal similarities and differences, tribal aspirations, cultural identities of Karnataka and tribals, tribal elder worship, tribal mother culture, tribal beliefs, tribal animal husbandry, tribal languages, tribal cultural leaders, If we look at the life of the tribal communities, we will get a deep understanding of them. These are the identities of the tribal culture which need to be noticed and who is not considering them. It is imperative to study the identities of the tribes in the face of new ideas on such issues because there are chances that these are dying out day by day.